2018
DOI: 10.1029/2017wr021523
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bed‐Load Transport on Flow Resistance of Step‐Pool Channels

Abstract: This study investigates the influence of bed‐load transport on flow resistance and bed stability in steep step‐pool channels. A total of 86 flume experiments was performed. Stable step‐pool sequences were formed with increasing discharge under clear‐water conditions. The addition of fine bed‐load material to the flow led to a decrease in bed roughness and an increased mobility of step‐forming clasts. Velocity measurements showed that bed‐load transport significantly decreased flow resistance and increased near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 52 publications
2
25
0
Order By: Relevance
“…Step-pool stability is reported to be closely related to discharge magnitude, sediment transport and local scour (Comiti et al, 2009;Zimmermann, 2009;Curran, 2012;Waters and Curran, 2012;Zhang et al, 2016Zhang et al, , 2018Hohermuth and Weitbrecht, 2018) and all of these influencing factors are intensified during the rising limb. Therefore, the rising limb was focused on in our experiment.…”
Section: Hydrograph Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Step-pool stability is reported to be closely related to discharge magnitude, sediment transport and local scour (Comiti et al, 2009;Zimmermann, 2009;Curran, 2012;Waters and Curran, 2012;Zhang et al, 2016Zhang et al, , 2018Hohermuth and Weitbrecht, 2018) and all of these influencing factors are intensified during the rising limb. Therefore, the rising limb was focused on in our experiment.…”
Section: Hydrograph Designmentioning
confidence: 99%
“…> 0.5) indicates that most of the potential energy at the step entrance is dissipated and thus, the flow velocity increase is largely limited and even negative sometimes. If the kinetic energy of the flow is well controlled, the capability of the flow to mobilize and transport grains will be limited (Hohermuth and Weitbrecht, 2018). Therefore, the energy dissipation ratio is related to bed stability and is a crucial parameter for effective riverbed consolidation by stabilization structures like step-pools (Wang et al, 2012).…”
Section: Energy Dissipationmentioning
confidence: 99%
“…Several studies in the last decades have increased our knowledge on how step-pool systems function, especially with regard to the step-forming mechanisms (Chin, 1999;Curran, 2007;Golly et al, 2019;Saletti et al, 2016;Zimmermann et al, 2010), the stability of steps (Waters and Curran, 2012;Zhang et al, 2019Zhang et al, , 2018Zimmermann et al, 2010), the links between channel and hillslope dynamics (Golly et al, 2017;Molnar et al, 2010), and the relations between flow magnitude, flow resistance, and sediment transport (Comiti et al, 2009a;Hohermuth and Weitbrecht, 2018;Saletti et al, 2015;Turowski et al, 2009;Zimmermann, 2010). Field studies and flume experiments highlighted how boulder protrusion (Yager et al, 2018(Yager et al, , 2007, grain clustering (Johnson, 2017), and the supply of fine sediment (Johnson et al, 2015) impact flow resistance and therefore channel stability and sediment transport in step-pool channels. Furthermore, the importance of granular interactions for step formation and stability has been previously recognized (Church and Zimmermann, 2007;Saletti et al, 2016) and it has been suggested that steps are more stable than predicted because of the emergence of force chains in the transversal direction that keep them in place even when subjected to higher shear stress (Bouchard et al, 2001;Church and Zimmermann, 2007;Saletti and Hassan, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the experiments conducted for this study, we obtained topographic and hydraulic data for 86 step-pool experiments published by Hohermuth and Weitbrecht (2018). The experiments were conducted in a 1:20 Froude-scaled model of a mountain stream, utilizing a range of bed slopes (8 -11 percent), channel widths (15 -35 cm), and discharges.…”
Section: Additional Experimentsmentioning
confidence: 99%